PERATURAN TATA RUANG DALAM MEMBERIKAN IZIN MENDIRIKAN BANGUNAN PADA RUMAH IBADAH - Theresia Simanullang, Berty; Tobing, Maria; Helmi, Helmi (Fakultas Hukum Universitas Jambi, 2021)
The Indonesian state is obliged to facilitate the people living within its territory so that they can live harmoniously side by side. Pancasila as the basis of the state strives to create harmony in the population including harmony in religion. Pancasila has been agreed to be the basis of the state and functions to protect religious plurality in Indonesia, one of which is in establishing houses of worship as stated in the 1945 Constitution Article 29 paragraph (2) which reads: